Cognitive mediation of clinical improvement after intensive exposure therapy of agoraphobia and social phobia. - Vögele, C; Ehlers, A; Meyer, A; Frank, M; Hahlweg, K; Margraf, J (2010)
BACKGROUND: The present study investigated cognitive mediation of clinical improvement in patients with agoraphobia (N=427) or social phobia (N=98) receiving high-density exposure therapy in a naturalistic clinical treatment setting. METHODS: Patients were assessed before therapy, 6 weeks after the end of therapy, and 1 year thereafter, using a self-report assessment battery. Lower level mediation analyses provided support for the notion that cognitive changes partially mediate clinical improvement after exposure therapy. RESULTS: Changes in cognitions relating to physical catastrophes mediated treatment outcome only for patients with agoraphobia, whereas changes in cognitions about loss of control mediated outcome for both agoraphobia and social phobia patients. Changes in relationship satisfaction did not mediate symptomatic improvement. CONCLUSIONS: The results extend previous findings by demonstrating mediation in an unselected clinical sample and by providing evidence for the specificity of mediation effects. They further support the importance of cognitive changes in cognitive-behavior therapy.